2020
DOI: 10.1093/mnrasl/slaa092
|View full text |Cite
|
Sign up to set email alerts
|

A low-mass stellar companion to the young variable star RZ Psc

Abstract: RZ Psc is a young Sun-like star with a bright and warm infrared excess that is occasionally dimmed significantly by circumstellar dust structures. Optical depth arguments suggest that the dimming events do not probe a typical sightline through the circumstellar dust, and are instead caused by structures that appear above an optically thick mid-plane. This system may therefore be similar to systems where an outer disc is shadowed by material closer to the star. Here, we report the discovery that RZ Psc hosts a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This wide companion is classified as a white dwarf candidate with a mass of 0.48-0.58 M ⊙ (depending on whether a pure-He or pure-H atmosphere is supposed, Gentile Fusillo et al 2019). Recently, Kennedy et al (2020) reported the discovery of a low mass companion of RZ Psc at a projected separation of 23 au. The other three stars, HD 15407, HD 23514, and V488 Per, are all reported to have wide-orbit companions, the projected separations are ρ p = 1050, 365, and 12300 au, respectively (Melis et al 2010;Rodriguez et al 2012;Zuckerman 2015).…”
Section: Wide Separation Companionsmentioning
confidence: 99%
“…This wide companion is classified as a white dwarf candidate with a mass of 0.48-0.58 M ⊙ (depending on whether a pure-He or pure-H atmosphere is supposed, Gentile Fusillo et al 2019). Recently, Kennedy et al (2020) reported the discovery of a low mass companion of RZ Psc at a projected separation of 23 au. The other three stars, HD 15407, HD 23514, and V488 Per, are all reported to have wide-orbit companions, the projected separations are ρ p = 1050, 365, and 12300 au, respectively (Melis et al 2010;Rodriguez et al 2012;Zuckerman 2015).…”
Section: Wide Separation Companionsmentioning
confidence: 99%
“…The latter authors first suggested that RZ Psc is surrounded by circumstellar disk with the central cavity free (or almost free) of matter. This assumption was confirmed by de Wit et al (2013): a bright mid-IR excess was found in WISE observations of RZ Psc, fitted by black-body radiation with temperature ≈ 500 K. They assumed that the star is surrounded by the dusty ring with inner radius 0.4-0.7 AU and this assumption was recently confirmed by Kennedy et al (2020). They discovered that RZ Psc hosts a 0.12 M companion at a projected separation of 23 AU.…”
Section: Introductionmentioning
confidence: 74%
“…There is no sign of cold dust (debris outside tens of astronomical units), although its presence cannot be ruled out due to the lack of far-infrared/millimeter observations. High-contrast, ground-based imaging recently obtained with VLT/SPHERE shows that RZ Psc hosts a 0.12 M ☉ companion at a projected separation of 22 au and concludes that the disk (the source of the infrared excess) orbits the primary star (Kennedy et al 2020). The low-mass component is expected to have a significant impact on the disk itself, such as truncating the disk outer edge and heavily stirring the remaining planetesimals.…”
Section: Introductionmentioning
confidence: 96%